Exploring the interplay of narrative in music videos and its influence on listeners’ experience / Nur Saiyidatul Hajar Zaini and Norman Yusoff - Zaini, Nur Saiyidatul Hajar; Yusoff, Norman (College of Creative Arts, 2025)
This study explored the effects of music video narratives on listeners and their experiences to fully understand its impact and fill in the study gap on the subject. As the music industry flourished, so did the music videos industry as they are used to promote and convey the message of the songs. A focus group consisting of five people who analyzed music videos and their meanings was conducted. Their responses were analyzed with narrative analysis and the results show that the complexity and simplicity of music videos can significantly affect the audience. The emotional effects are maximized when the lyrics of the songs are related to the scenes or if the story is creatively executed to give the audience the emotional impact intended by the artist. The mix of visual and auditory elements, plus the limited time frame it had to promote the song and spread its message gave the audience a wide range of emotional effects. With their narrative often being left open to interpretations, it encourages people to make their own theories and is even likened to a form of art. For further research on the subject, a case study can be created on a specific music video or a series of it and dive into the message the artist is trying to convey and how the audience interprets it.